Determination of the intensity of a power jump session by means of heart rate monitoring - Juliano Fernandes da Silva; Lorival José Carminatti; Luiz Guilherme Antonacci Guglielmo; Talita Grossl (Universidade Federal de Santa Catarina, 2008)
A Power Jump (PJ) session is considered to be a safe and easy class that also involves intermittent exercises that prolong the time to exhaustion. However, there is not enough information about this subject in the literature. The purpose of this study was to determine the intensity of a PJ session by means of heart rate (HR) monitoring. Eleven physically active females participated in the study (age: 21.7 ± 1.9 years; body mass: 59.3 ± 4.8 kg; height: 162.6 ± 5.6 cm; percentage body fat: 22.6 ± 3.2 %). Participants were asked to perform an incremental test (IT), in order to obtain values for oxygen uptake (VO2), maximal heart rate (HRmax), heart rate deflection point (HRDP) and energy expenditure (EE). The HR of the subjects was monitored during a special type of Power Jump session called "mix nine" on two different occasions. According to the HRDP values, physiological domains could be divided into three exercise intensity classes: moderate, heavy and severe. Descriptive statistics were adopted (mean ± SD). Student's t test was used to compare HR and EE between PJ1 and PJ2. For comparisons between domains, two-way ANOVA and the Scheffé test were used. The level of significance was set at p<0.05. Mean HRmax obtained during the IT was 195±10bpm. The velocities, HR and %HRmax corresponding to HRDP and 80% of HRDP were 10.1±0.95km.h-1, 178±7bpm and 91.7±4.0%; and 8.1±0.76km.h-1, 143±5bpm and 73.4±3.2%, respectively. Values for HRmean and EE were significantly different when PJ1 (161±11bpm, 386±58.2kcal) and PJ2 (156±10bpm, 355.1±53.8kcal) were compared. The times spent in each exercise intensity domain were: heavy 51±14.5%; severe 27±19.7% and moderate 23±8.7%. These results show that the subjects spent most of the time in the heavy exercise domain which, in turn, appears to be the most indicated for improving aerobic capacity. Resumo O Power Jump (PJ) caracteriza-se como uma aula segura, de fácil execução, com ações intermitentes retardando a fadiga. Contudo, são escassos os estudos específicos sobre o assunto. O objetivo deste estudo foi determinar a intensidade da aula de PJ por meio da freqüência cardíaca (FC). Participaram do estudo 11 mulheres praticantes da modalidade (21,7±1,9 anos; 59,3±4,8kg; 162,6±5,6cm; 22,6±3,2 %G). Os indivíduos foram primeiramente submetidos a um teste incremental em esteira ergométrica (TI), obtendo valores de consumo de oxigênio (VO2), FC máxima (FCmax), ponto de deflexão da FC (PDFC) e gasto calórico (GC). Os indivíduos tiveram sua FC monitorada em duas aulas da modalidade do mix nove. Os domínios fisiológicos foram delimitados de acordo com os valores de PDFC em três domínios de esforço: severo, pesado e moderado. Foi empregada a estatística descritiva (média±DP). Para comparações de FC e GC entre PJ1 e PJ2, foi realizado o teste t de Student, e, para comparações entre os domínios a análise de variância Two-way, complementada pelo Scheffé test. Foi adotado p<0,05. A FCmax no TI foi de 195±10 bpm. A velocidade, FC e %FCmax correspondentes ao PDFC e 80% do PDFC foram 10,1±0,95km.h-1, 178±7 bpm e 91,7±4,0%; 8,1±0,76km.h-1, 143±5 bpm; 73,4±3,2%, respectivamente. Foi significativa a diferença da FCmédia e GC entre PJ1 (161±11 bpm, 386±58,2kcal) e PJ2 (156±10 bpm, 355,1±53,8 kcal). O tempo de permanência no domínio pesado foi de 51±14,5%; severo 27±19,7% e 23±8,7% no moderado. Pode-se concluir que as alunas permaneceram maior parte das aulas no domínio pesado, intensidade que é adequada para o aprimoramento da capacidade aeróbia.